0715 Diagnosis of Sleep Disordered Breathing in Patients with Interstitial Lung Disease: A Retrospective Evaluation of Polysomnogram and Home Sleep Apnea Testing Using Peripheral Arterial Tonometry. (25th May 2022) - Kelly, Bryan; Moua, Teng; Escalante, Patricio
Abstract: Introduction: Previous studies have shown that sleep disordered breathing (SDB) is common in patients with Interstitial Lung Disease (ILD), and oximetry is often used for screening prior to further diagnostic testing. Current guidelines recommend polysomnography (PSG) for diagnosis of SDB in patients with significant pulmonary disease, however, home sleep apnea tests (HSAT) are increasingly used in clinical practice for a variety of reasons despite lack of evidence regarding accuracy in this population. In this study, we evaluate the correlation between screening oximetry, a commercial brand HSAT (WatchPAT®) and PSG to examine the diagnostic accuracy of this HSAT technology in patients with ILD. Methods: The institution electronic medical record was screened for patients with a diagnosis code for ILD who underwent screening oximetry followed by PSG or HSAT using peripheral arterial tonometry from July 1, 2012 to present. Clinical review confirmed presence of ILD according to American Thoracic Society guidelines. Among the respective cohorts, Paired Wilcoxon Test was used to compare the oximetry 4% oxygen desaturation index (ODI) to the HSAT ODI and PSG apnea-hypopnea index (AHI) as well as percent time spent below oxyhemoglobin saturation of 89%. Spearman correlation was used to correlate the oximetry ODI and parameters of SDB on HSAT and PSG. Results: Data was analyzed for 25 patients who had undergone oximetry/HSAT and for 25 patients who had undergone oximetry/PSG. Oximetry ODI showed no significant difference from PSG AHI (p = 0.2635) or between HSAT ODI (p = 0.0755), and no difference was seen in hypoxic time between oximetry and PSG (p = 0.9789). Hypoxic time on HSAT was significantly longer than that on oximetry (p < 0.001). Using HSAT ODI as the standard, HSAT AHI and respiratory disturbance index (RDI) showed rs of 0.9638 and 0.8913 respectively, while oximetry ODI was 0.3893. Compared to PSG AHI, the PSG RDI and oximetry ODI rs were 0.9759 and 0.7407 respectively. Conclusion: Among patients with ILD, screening oximetry appears to correlate more strongly with indices of SDB and hypoxic time on PSG rather than HSAT. Further studies are warranted to evaluate efficacy of additional HSAT testing modalities in this patient population. Support (If Any):